Metaphorical Terms as Part of Construction Terminology in English and Russian - Valeriya A. Katysheva; Evgeniya Yu. Kunitsyna (СибСкрипт)
: The science of cognitive-discursive terminology and linguistic metaphor is developing very fast. The range of professional metaphors expands with new factual data. In this respect, metaphorization is an effective tool for expanding the terminological system in the fi        of building and construction. The authors used the lexicological, componential, cognitive, and statistical methods to analyze 2,134 metaphorical terms in the construction discourse registered in the English-Russian Construction Dictionary (1995). The part-of-speech and quantitative parameters demonstrated the prevalence of di- and trilexemic models over mono- and polylexemic ones. This phenomenon can be explained by the dual nature of metaphorization, as well as by the terminological precision of scientifiс and technical discourse. The conceptual metaphor approach made it possible to identify the source domain behind each metaphorical transfer. The thematic categorization revealed the following metaphorical models: anthropomorphic (914 units, 43%), artifactual (633 units, 30%), nature-morphic (435 units, 20%), and eschatological (152 units, 7%).